Defining the Impact of Non‐Native Species - JONATHAN M. JESCHKE; SVEN BACHER; TIM M. BLACKBURN; JAIMIE T. A. DICK; FRANZ ESSL; THOMAS EVANS; MIRIJAM GAERTNER; PHILIP E. HULME; INGOLF KÜHN; AGATA MRUGAŁA; JAN PERGL; PETR PYŠEK; et al. (Conservation Biology, 2014)
Non‐native species cause changes in the ecosystems to which they are introduced. These changes, or some of them, are usually termed impacts; they can be manifold and potentially damaging to ecosystems and biodiversity. However, the impacts of most non‐native species are poorly understood, and a synthesis of available information is being hindered because authors often do not clearly define impact. We argue that explicitly defining the impact of non‐native species will promote progress toward a better understanding of the implications of changes to biodiversity and ecosystems caused by non‐native species; help disentangle which aspects of scientific debates about non‐native species are due to disparate definitions and which represent true scientific discord; and improve communication between scientists from different research disciplines and between scientists, managers, and policy makers. For these reasons and based on examples from the literature, we devised seven key questions that fall into 4 categories: directionality, classification and measurement, ecological or socio‐economic changes, and scale. These questions should help in formulating clear and practical definitions of impact to suit specific scientific, stakeholder, or legislative contexts. Definiendo el Impacto de las Especies No‐Nativas